Effect of Fluoride Varnish application on Primary Dentition among Preschool Children in Dharan: A Randomized Controlled Trial - Agrawal, Santosh Kumari; Shrestha, Ashish; Bhagat, Tarakant (Journal of Nepalese Association of Pediatric Dentistry, 2022)
Introduction: Topical application of fluoride varnish on the tooth surface prevents the dissolution rates of tooth materials and increases the re-precipitation of lost minerals.Objective: To assess the effectiveness of fluoride varnish application in primary dentition among preschool children at high risk of dental caries.Methods: A randomized controlled trial was conducted with two parallel-group, comprising 3–5-year-old children, 100 in each group (Fluoride varnish or Placebo varnish). Dental caries were recorded at baseline, three- and six-month using Caries Assessment and Treatment Instrument (CAST) scoring system. Statistical analysis was done using the Chi-square test for categorical data, Mann-Whitney U test, independent t-test, and Wilcoxon Signed Ranks test for quantitative data. The level of significance was set at p